Deep learning application for abdominal organs segmentation on 0.35 T MR-Linac images - Zhou, You; Lalande, Alain; Chevalier, Cédric; Baude, Jérémy; Aubignac, Léone; Boudet, Julien; Bessieres, Igor (Frontiers in Oncology, 2024)
Linear accelerator (linac) incorporating a magnetic resonance (MR) imaging device providing enhanced soft tissue contrast is particularly suited for abdominal radiation therapy. In particular, accurate segmentation for abdominal tumors and organs at risk (OARs) required for the treatment planning is becoming possible. Currently, this segmentation is performed manually by radiation oncologists. This process is very time consuming and subject to inter and intra operator variabilities. In this work, deep learning based automatic segmentation solutions were investigated for abdominal OARs on 0.35 T MR-images. One hundred and twenty one sets of abdominal MR images and their corresponding ground truth segmentations were collected and used for this work. The OARs of interest included the liver, the kidneys, the spinal cord, the stomach and the duodenum. Several UNet based models have been trained in 2D (the Classical UNet, the ResAttention UNet, the EfficientNet UNet, and the nnUNet). The best model was then trained with a 3D strategy in order to investigate possible improvements. Geometrical metrics such as Dice Similarity Coefficient (DSC), Intersection over Union (IoU), Hausdorff Distance (HD) and analysis of the calculated volumes (thanks to Bland-Altman plot) were performed to evaluate the results. The nnUNet trained in 3D mode achieved the best performance, with DSC scores for the liver, the kidneys, the spinal cord, the stomach, and the duodenum of 0.96±0.01, 0.91±0.02, 0.91±0.01, 0.83±0.10, and 0.69±0.15, respectively. The matching IoU scores were 0.92±0.01, 0.84±0.04, 0.84±0.02, 0.54±0.16 and 0.72±0.13. The corresponding HD scores were 13.0±6.0 mm, 16.0±6.6 mm, 3.3±0.7 mm, 35.0±33.0 mm, and 42.0±24.0 mm. The analysis of the calculated volumes followed the same behavior. Although the segmentation results for the duodenum were not optimal, these findings imply a potential clinical application of the 3D nnUNet model for the segmentation of abdominal OARs for images from 0.35 T MR-Linac.